Concentrations, pollution indices and health risk assessment of heavy metals in road dust from two urbanized cities of Pakistan: Comparing two sampling methods for heavy metals concentration. (February 2020) - Qadeer, Abdul; Saqib, Zulfiqar Ahmad; Ajmal, Zeeshan; Xing, Chen; Khan Khalil, Saira; Usman, Muhammad; Huang, Yanping; Bashir, Safdar; Ahmad, Zulfiqar; Ahmed, Saeed; Thebo, Khalid Hussain; Liu, Min
Graphical abstract: Highlights: Deposit gauge method showed higher pollution level of heavy metals in the dust. Sweeping tools method is a commonly used method showed less pollution. General Bus Stand in both cities showed greater heavy metals concentrations. There were potential carcinogenic health risks associated with Cd. Abstract: Lahore and Faisalabad are two highly populated metropolitans of Pakistan. The increasing number of vehicles and urbanization resulted in the contamination of urban road dust with heavy metals, which can expose residents to health hazards. The aim of this research was to determine the road dust heavy metal (Cu, Ni, Cd, Pb, and Zn) concentrations, their distribution, comparison, and their potential health risk assessment for local people. Herein, two sampling methods, namely deposit gauge method (DGM) and sweeping tools method (STM), were used to collect road dust samples in eight similar major road intersections. Dust collected by DGM (gravitational pull of air dust) showed higher heavy metals concentration than STM in both cities, which might be associated to the smaller dust particles collected in the DGM. Among sites, concentrations of heavy metals were the highest in dust obtained from the General Bus Stand in both cities. Dominant metals were Zn and Pb with an average concentration of 95.5 and 56.8 mg kg −1, respectively while Cd was the lowest in Lahore. Similarly, the concentration of Pb and Zn were also high in Faisalabad with an average of 90.4 and 49.5 mg kg −1 and Cd was the lowest. Overall, Lahore showed higher pollution levels than Faisalabad. The risk assessment results of the DGM indicated that there were potential carcinogenic health risks associated with Cd, as his values were close or exceeded the permissible limit of 1 × 10 −4 . Non-carcinogenic risk assessment results were lower than value 1 for both cities which means there were no non-carcinogenic hazards for the residents. Higher Enrichment ratio (ER) and geo accumulation index (Igeo ) showed increasing heavy metal pollution in both cities is a serious concern. Therefore this research provides a vital base and help to authorities for pollution control strategies, remediation, and regular monitoring in order to improve eco-sustainable cities and health of urbanites.